Christianity between Civilization and Barbarism in Domingo Faustino Sarmiento (1840-1850) - Podestá, Agustín (Teología, 2019)
This article emerges from the thesis for the Degree in Theology with a Specialization in Church History, entitled: The Catechisms of Sarmiento. Contextualization and comment, defended in June 2019. We propose here to glimpse how Christianity, accor- ding to Sarmiento’s conception, has a leading role in the conformation of the civilized and the barbaric; the Christian religion as an element or note of civilization or barba- rism. This approach will be based on an analysis of Sarmiento’s books: Facundo o civilización y barbarie, Recuerdos de provincia y La conciencia de un niño written betwe- en 1840 and 1850.